The Hematopoietic Organ: A Cornerstone for Wolbachia Propagation Between and Within Hosts - Braquart-Varnier, Christine; Raimond, Maryline; Mappa, Gaëtan; Chevalier, Frédéric D.; Le Clec’h, Winka; Sicard, Mathieu (Frontiers in Microbiology, 2015)
Wolbachia is an intracellular alpha-proteobacterium which is transmitted vertically from mother to offspring but also frequently switches horizontally from one host to another. Our hypothesis is based on the role of immune cells and the organs that produce them, the Hematopoietic Organs (HOs), as primordial niches for the propagation of Wolbachia via hemocytes both (i) within hosts: to initiate and maintain the systemic infection and (ii) between hosts: to promote both vertical and horizontal transmission of Wolbachia. Therefore, we review some fundamental ideas underlying this hypothesis and go further with new empirical data that lead to a first close-up analysis of the potential role of HOs in Wolbachia propagation. The monitoring of the first steps of Wolbachia infection in horizontally infected host organs by TEM and qPCR suggests that (i) HOs are colonized early and extensively as soon as they are in contact with Wolbachia which find in these cells a favorable niche to multiply and (ii) infected HOs which expel hemocytes all lifelong can generate and maintain a systemic infection that could contribute to increase both vertical and horizontal propagation of these symbionts.